Nollywood films and students’ behaviour in Emmanuel Alayande College of Education, Oyo (2014)
This study investigated the influence of Nollywood films on the behaviour of young people, especially students in Nigerian Colleges of Education. The objective of the study was to assess the influence of negative themes in Nigerian Home video as reasons why some young people exhibit unruly and anti-social behaviour in Nigerian College of Education Campuses. Using survey research method, 386 respondents were drawn as sample size from Emmanuel Alayande College of Education, Oyo through a stratified sampling technique. 8 students were drawn for focus group discussion (FGD) and 3 lecturers for the in-depth interview session. Findings from the study indicated that majority of students regularly watched Nollywood films like comedy, romantic/sexual and action/horror; they watched them for cultural acquisition and socialization. However these movies show negative themes which promote some of the antisocial behaviours exhibited by students who watched them, thus watching these movies could influence their behaviour negatively. Nigerian Broadcasting Cooperation (NBC) and National Film and Video Censors Board (NFVCB) should encourage movie producers to focus more on the fundamental and tripartite functions of drama, which is to entertain, educate and inform the audience.